2018
DOI: 10.1111/jam.14030
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon-degrading bacteria in deep-water subarctic sediments (Faroe-Shetland Channel)

Abstract: Oil and gas exploration in the FSC occurs at depths >1000 m but baseline environmental data necessary for the assessment of ecosystem recovery to prespill conditions in the event of an oil spill are lacking. This study will contribute to our ability to assess the impact of oil release in the FSC and guide the direction of bioremediation strategies tailored to the area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 68 publications
(149 reference statements)
3
25
0
1
Order By: Relevance
“…This result was not unexpected, as it has been previously reported [33]. The taxa identified in the microbiome of the diesel-degrading consortium are in agreement with previous works, where it has been shown what Pseudomonas is one of the most abundant genera on hydrocarbon-polluted soils [34,57,58] and Aquabacterium and Chryseobacterium are also common members in hydrocarbon-degrading bacterial communities [58,59]. Although Pseudomonas also rules the degradation of PAHs in sediments [60], other genera present in the diesel-degrading consortium belonging to the Sphingomonadaceae family have also been previously reported to be responsible for the degradation of different PAHs [61,62].…”
Section: Resultssupporting
confidence: 92%
“…This result was not unexpected, as it has been previously reported [33]. The taxa identified in the microbiome of the diesel-degrading consortium are in agreement with previous works, where it has been shown what Pseudomonas is one of the most abundant genera on hydrocarbon-polluted soils [34,57,58] and Aquabacterium and Chryseobacterium are also common members in hydrocarbon-degrading bacterial communities [58,59]. Although Pseudomonas also rules the degradation of PAHs in sediments [60], other genera present in the diesel-degrading consortium belonging to the Sphingomonadaceae family have also been previously reported to be responsible for the degradation of different PAHs [61,62].…”
Section: Resultssupporting
confidence: 92%
“…Alcanivorax was not represented in the 20 most abundant taxa in the Hatton–Rockall Basin deep‐sea sediments in this study. Alcanivorax dominated an enriched HDB community from continental shelf sediments of the FSC but was absent from deepwater sediments (500–1,000 m) in the same area (Gontikaki et al, ; Potts et al, ). This study confirms the piezosensitivity of Alcanivorax that may explain its absence from deepwater hydrocarbon‐degrading microbial communities following the DwH oil spill (Kimes et al, ; Scoma et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported a synchronous negative effect of deep‐sea conditions of high P and low T on the growth of Halomonas isolates (Kaye & Baross, ). Halomonas also represented 5%–9% of taxa in enrichment cultures from continental shelf sediments in the FSC but was absent from deepwater libraries (Gontikaki, Potts, Anderson, & Witte, ; Potts et al, ). Despite being previously encountered in cold, oil‐contaminated marine environments (Deppe, Richnow, Michaelis, & Antranikian, ; Gerdes, Brinkmeyer, Dieckmann, & Helmke, ), Marinobacter was encountered in higher relative abundance at 0.1 MPa and 20°C in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, most of the phylotypes detected as differentially abundant in the shallow group are related to hydrocarbon degradation, such as Microcoleus ( Sánchez et al, 2005 ), Ahrensia ( Gontikaki et al, 2018 ), and Thermococcus ( Mardanov et al, 2009 ), and more specific genera such as Tropicimonas ( Harwati et al, 2009 ), Dethiosulfatibacter ( Muangchinda et al, 2013 ), Cellulosimicrobium ( Qin et al, 2018 ), Roseobacter ( Liu et al, 2016 ), Prolixibacter ( Li et al, 2012 ), Desulfuromusa ( Ramos et al, 2013 ), Oceanicola ( Hassanshahian and Boroujeni, 2016 ), and Salinivibrio ( Selvarajan et al, 2017 ) are involved in aromatic hydrocarbons degradation, supporting our hypothesis that this abiotic factor modulates the bacterial communities in the shallow region. We also found other genera such as Psychrilyobacter , which participates in the anaerobic degradation of organic matter ( Graue et al, 2012 ), and Dehalococcoides ( Nuzzo et al, 2017 ) and Dehalobacterium ( Yimiti et al, 2011 ), which detoxify anoxic contamination in marine sediments, such as polychlorinated biphenyls.…”
Section: Discussionmentioning
confidence: 99%